TOWARDS A 6CS POSITIONING TYPOLOGY OF MEDICAL TOURISM DESTINATION IN INDIA - KEITH NG YONG NGEE (Centre For Tourism Planning and Development, 2011)
Medical Tourism was coined when people started looking for cost-effective treatments internationally. The success of this industry depends on the collaboration between private medical care providers and the tourism industry that focused on patients seeking critical and complex surgeries and other forms of specialized treatment. The main objective of this paper is to examine the perspectives of different stakeholders to position India as a global healthcare and medical tourism destination.Grounded theory was chosen as the main research methodology. Grounded theory is a systematic, inductive approach to help understand complex social processes. The main motivation that encouraged this choice is the ability of grounded theory to handle the emergence of problems identified by participants in a study. The principal data collection method was interview of likely stakeholders in the medical tourism industry in India. Using the constant comparison technique, data from interviews were coded and grouped into similar categories to identify patterns.This study highlighted the importance of branding in positioning India as a medical hub and the importance of public-private partnerships in exploring the emerging avenues in healthcare tourism. The research results will also help in gaining some valuable insights which will help all the interest groups and beneficiaries to make maximum advantage of healthcare travel.